Song acts writings on words and music - Kramer, Lawrence; Leppert, Richard D.; Bernhart, Walter (Word and music studies, 2017)
This volume collects twenty of Lawrence Kramer’s seminal writings on art song (especially Lieder), opera, and word-music relationships. All examine the formative role of culture in musical meaning and performance, and all seek to demonstrate the complexity and nuance that arise when words and music interact. The diverse topics include words and music, music and poetry, subjectivity, the sublime, mourning, sexuality, decadence, orientalism, the body, war, Romanticism, modernity, and cultural change. Several of the earlier essays have been revised for this volume, which also contains a preface by the author and a foreword by Richard Leppert. The volume should be essential reading for scholars, students, performing musicians, and other music-lovers interested in musicology, word-music relationships, cultural studies, aesthetics, and intermediality.
Keywords: Musical criticism; Songs : History and criticism; Opera; Music and literature